Effects of D2-dopamine and alpha-adrenoceptor antagonists in stress induced changes on immune responsiveness of mice - Fiserová, Anna; Starec, Miroslav; Kuldová, Markéta; Kovárů, Hana; Páv, Marek; Vannucci, Luca; Pospísil, Miloslav (Journal of neuroimmunology, 2002)
The involvement of catecholamine receptors (alpha-adrenergic, D2-dopamine (DA)) was investigated in restraint stress influenced immune responses with concomitant changes of G-protein signal transduction. Impairment of the spleen morphology, TH1/TH2 cytokine network and natural killer (NK) cell function was observed. In vivo administration of specific antagonists prior to restraint stress reversed the immunosuppression. These findings demonstrate that D2-type dopaminergic mechanism represents the dominant component in regulation of Galphas/Galphai(1,2)/Galphaq/11-protein signal transduction and contribute to cell responses at postreceptor level of both, central nervous and immune systems. G-protein-coupled receptors (GPCRs) can modulate cytokine production and may play a regulatory role in immune effector mechanisms.
Keywords: alfa blokátory; fyziologický stres; Dopamine D2 Receptor Antagonists; Neuroimmunomodulation; mozek; neurosekreční systémy; antagonisté dopaminu; T-Lymphocytes; imunitní systém; alfa-adrenergní receptory; Dopamine Antagonists; Leukocytes, Mononuclear; Phenotype; Immune System; katecholaminy; proteiny vázající GTP; zvířata; myši; receptory dopaminu D2; Adrenergic alpha-Antagonists; B-lymfocyty; buňky NK; Mice; Killer Cells, Natural; Stress, Physiological; Mice, Inbred CBA; antagonisté dopaminu D2; Male; Brain; fenotyp; Spleen; B-Lymphocytes; neuroimunomodulace; leukocyty mononukleární; Catecholamines; T-lymfocyty; Animals; myši inbrední CBA; Receptors, Adrenergic, alpha; mužské pohlaví; Neurosecretory Systems; GTP-Binding Proteins; slezina; Receptors, Dopamine D2